Evaluation of Bovine Derived Xenograft Combined with Bioresorbable Collagen Membrane in Treatment of Intrabony Defects - Gorkhali, Ranjita Shrestha; Pradhan, Shaili; Shrestha, Rejina; Agrawal, Shweta; Lamicchane, Krishna; Koirala, Pramod Kumar; Shrestha, Benju (Journal of Nepalese Society of Periodontology and Oral Implantology, 2020)
Introduction: Treatment of periodontal diseases done by surgical therapy depends upon extent and severity of disease. The ultimate goal of periodontal reconstructive surgery is to regenerate tissues destroyed during periodontal disease. Objective: To evaluate the effectiveness of bovine-derived xenograft with collagen membrane in treatment of intrabony defects by comparing it with open flap debridement alone. Methods: This non-randomised controlled trial was conducted after ethical clearance, at Bir hospital from 2018 March to 2019 April. The study recruited 38 patients by convenience sampling, age from 25-44 years, with chronic periodontitis, and willing to sign informed consent. Intrabony defects were treated by open flap debridement with bovine-derived xenograft and bioresorbable collagen membrane (Test group) and open flap debridement alone (Control group). Probing pocket depth, clinical attachment level, gingival recession, oral hygiene status, and gingival status were assessed at baseline and six months. Results: Six months after therapy, in Test group probing pocket depth reduction was 5.2 mm and gain in mean clinical attachment level was 4.3 mm. In Control group, mean probing pocket depth reduction was 3.8 mm and mean gain in clinical attachment level was 2.7 mm. The test treatment resulted in statistically higher probing pocket depth reduction and clinical attachment level gain than Control group. Conclusion: Both therapies resulted in significant probing pocket depth reductions and clinical attachment gains, and treatment with open flap debridement with bovine-derived xenografts and collagen membrane resulted in significantly higher probing pocket depth reduction and clinical attachment gain than treatment with open flap debridement alone.